ILRI 40 years keynote address: Livestock and economic well-being - Nwanze, K. (International Livestock Research Institute, 2014)
Keynote address by Kanayo Nwanze, President, International Fund for Agricultural Development (IFAD) at the ILRI@40 Conference: Livestock-based options for sustainable food and nutritional security, economic well-being and healthy lives, Addis Ababa, Ethiopia, 6–7 November 2014.